514 FRAILTY IN OSTEOARTHRITIS AND THE INFLUENCE OF CO-MORBIDITY. (14th June 2021) - Cook, M J; Verstappen, S M M; Lunt, M; O'Neill, T W
Abstract: Introduction: Risk factors for frailty, including low physical activity and chronic pain, are common among people with osteoarthritis. The aim of this analysis was to determine the association between osteoarthritis and frailty and to determine whether comorbidities interact additively with OA to increase the likelihood of frailty. Methods: Men and women aged 40-69 years who contributed to the UK Biobank were analysed. Data about self-reported physician-diagnosed diseases was collected, as well physical measurements, including hand-grip strength. Frailty (robust, pre-frail, frail) was assessed using a modified frailty phenotype, comprising five components: low grip strength, slow walking speed, weight loss, low physical activity, and exhaustion. The association between osteoarthritis and the frailty phenotype was determined using negative binomial regression, adjusting for age, sex, body mass index, smoking status, and Townsend deprivation score. We calculated the attributable proportion of risk of frailty due to additive interaction between osteoarthritis and common co-morbidities (cardiovascular disease, diabetes, COPD, and depression). Results: 457, 561 people were included, 35, 884 (7.8%) had osteoarthritis. The adjusted relative risk ratio (95% CI) for pre-frailty and frailty (versus robust), respectively was higher among people with (versus without) osteoarthritis: 1.58 (1.54, 1.62) and 3.41 (3.26, 3.56). There was significant additive interaction between the presence of osteoarthritis and each of the co-morbidities considered in increasing risk of frailty, particularly diabetes (attributable proportion of risk due to additive interaction with osteoarthritis (95% CI)), 0.49 (0.42, 0.55), coronary heart disease 0.48 (0.41, 0.55), and depression 0.47 (0.41, 0.53). Conclusions: Our results suggest that people with OA are at increased risk of pre-frailty and frailty. The mechanisms are not fully understood, though co-morbidity appears to contribute to the risk of frailty beyond the expected additivity of risk due to OA and co-morbidity. Early diagnosis and optimal management of co-morbidities in people with OA may be beneficial.